Kepribadian Tokoh Dalam Kumpulan Cerpen Menghardik Gerimis Karya Sapardi Djoko Damono: Kajian Psikoanalisis Sigmund Freud - Moch. Nur Riza Pratama Nugroho (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Short stories are a form of literary work that reflects life in society with characters that dominate the storyline. The research is based on the researcher's interest in the personality of the characters in the story. The qualitative method in this study focuses on the narration, description, and interpretation of the character's personality in the short story collection "Menghardik Gerimis" by Sapardi Djoko Damono based on Sigmund Freud's psychoanalysis theory. The data collected by the researcher is used as an object of analyzing the character's personality structure which includes id, ego, and superego. The method in collecting data, namely literature, reading, recording, data classification, and interpretation of the analyzed data. In the analysis, there are several aspects found, such as id (satisfaction, fantasy, curiosity, discomfort, and sexual urges), ego (delaying desires, accepting reality, rejecting desires, and making decisions, superego (religious awareness and manners). The conclusion of the research shows a deep understanding of the psychological aspects of the characters in the short story through Freud's psychoanalysis with a qualitative approach that emphasizes narration and interpretation, so as to provide deep insight into the personality aspects of the characters in literary works..